Incidence of sport disciplinary rules into those attitudes that may generate violence in sport - I. Jiménez; P. Martos (Asociación Española de Ciencias del Deporte, 2010)
Summary The current essay can be framed into a researching socio-juridical line about Sport Discipline, which is being done in the department of Physical and Sport Education in Granada's University. The aim of study is not the violence generated by means of sport -exogenous- but violence within the game field -endogenous-. Two parts have been clearly focused: the first, analysing and systematising juridical texts; and a second one about sociological research through a sample of 120 athletes. KEY WORDS: sport violence, sport discipline, attitudes.